Analysis of early hepatic artery thrombosis after liver transplantation. Issue 3 (27th February 2017) - Xue, Zhicheng; Chen, Maogen; Zhang, Xuzhi; Wang, Guodong; He, Xiaoshun; Wu, Linwei; Ma, Yi
Abstract : Background: Hepatic artery thrombosis (HAT) is one of the deadliest complications after orthotopic liver transplantation (OLT). This study aimed to identify risk factors and summarize the experience of HAT management after OLT. Methods: Clinical data of 407 adult patients who received OLT in our centres from July 2011 to December 2015 were retrospectively investigated. Results: The incidence rate of early HAT was 2.0% (8/407). Recipient/donor weight ratio ≥1.15 ( P = 0.02), presence of hepatic arterial reconstruction ( P < 0.001) and post‐operative blood transfusion ( P = 0.001) were significantly associated with early HAT in the univariate analysis and the only independent risk factor (odds ratio = 28.49) in binary logistic regression was the presence of hepatic arterial reconstruction. Among patients with early HAT, five received interventional revascularization while two received surgical revascularization and the remaining one received re‐transplantation. Their liver grafts were functioning well with patent hepatic artery until their last follow‐up, whereas one died from tumor recurrence at 31st month after transplantation. Conclusion: The presence of hepatic arterial reconstruction, recipient/donor weight ratio ≥1.15 and post‐operative blood transfusion were the main risk factors associated with early HAT. Prompt recognition of these factors, strict surveillance protocols and selective anticoagulation for patients at risk need to be evaluated. For patients with early HAT occurring within a week after transplantation, surgical re‐arterialization is preferential while interventional revascularization is recommended when it occurs beyond 7 days after transplantation.